The Effectiveness of The Function of The Industrial Office in Organizing The Expansion of Job Opportunities in Sukoharjo District - Adnan Syahrisal Dewanto; Labib Muttaqin (Proceeding International Conference Restructuring and Transforming Law, 2023)
This research aims to examine the concept of expanding job opportunities in Sukoharjo Regent Regulation No. 6 of 2017 and the effectiveness of the Sukoharjo Regency Industry and Manpower Service in implementing job expansion. It is hoped that this will be useful in providing insight and knowledge regarding the problem of workforce expansion that is occurring in Sukoharjo Regency and how the efforts of the Sukoharjo Regency Industry and Manpower Service to overcome the problem of workforce expansion. Research Results: The Concept of Expanding Job Opportunities in Sukoharjo Regent Regulation No. 67 of 2017 is an effort by the Regional Government and Community Institutions to create new jobs and develop available jobs. The aim is to create and develop productive and sustainable work opportunities by utilizing the potential of natural resources, human resources, community institutions, as well as appropriate technology. The effectiveness of the Sukoharjo Regency Industry and Manpower Service regarding Job Expansion has carried out its obligations well and effectively by making various regulations and policies. which is proven to have a positive impact on people who need work by opening opportunities for job expansion because regardless of special criteria, anyone can and deserves to get a job according to their wishes and all people have the right to live by doing their own work.